Russian life (Rich Frontier Pub. Co, 1993)
Continues: Soviet life, ISSN 0038-5549.Absorbed: Russian travel monthly.Formerly titled: Soviet Life.From 1995: 12/yearHas supplement: Chtenia, ISSN 1939-7240.